Efficacy of Intravenous Paracetamol Pretreatment for Prevention of Pain on Propofol Injection: A Randomized Placebo-Controlled Study - Hossain, Muhammad Sazzad; Islam, Md Shahidul; Rashid, Mohammad Mamunur; Babu, Md Anisur Rahman; Saha, Devashis (Journal of the Bangladesh Society of Anaesthesiologists, 2019)
Background and aim of study: Propofol, most frequently used intravenous anesthetic, is used forinduction of routine elective surgical procedure. Pain on propofol injection (POPI) still remains aconsiderable concern for the anesthesiologist. A number of techniques has been tried to minimize propofolinducedpain with variable results. Aim of this prospective randomized study is to observe the efficacy ofintravenous paracetamol injection as pretreatment for the prevention of pain caused by the propofolinjection. Materials and Methods: A total of 80 patients were selected in this study with the age group of 20 to 50years of either sex, ASA grade I and II, scheduled for routine elective surgical procedure under generalanesthesia with endotracheal intubation. The patients enrolled were divided randomly into two groupsof 40 patients each. Group I received 50 mg of intravenous paracetamol in 10 ml. Group II (placebogroup) received 10 ml of 0.9% intravenous normal saline. The patients were asked to report their painduring injection of propofol according to the McCririck and Hunter S scale.For all statistical tests, p<0.05 was taken to indicate a significant difference. Results: The incidence of pain experienced in paracetamol group is 25% patients and in saline group is70% patients, which is statistically significant p<0.05. The severity of POPI is also lower in paracetamolgroup than the saline group (p<0.05). The incidence of mild and moderate pain in paracetamol groupsversus saline group was 17.5% versus 45% and 7.5% versus 25% respectively p<0.05. There was nosevere pain recorded in any groups. Conclusion: Pretreatment of intravenous paracetamol is effectively reduces pain on propofol injection. JBSA 2019; 32(1): 24-27